(untitled) (Research, Society and Development, 2020)
The responses of the biometric parameters of the shrimp Litopenaeus vannamei in its initial stage, under low salinity and submitted to different photoperiods were evaluated under the climatic conditions of the Semi-Arid. Two independent experiments were conducted simultaneously for a period of 16 days at the Academic Unit of Serra Talhada, belonging to the Federal Rural University of Pernambuco, Serra Talhada, PE, Brazil. In each situation, a completely randomized design was adopted with four treatments and four repetitions: T1 - 0C: 24E, T2 - 12C: 12E (Natural light), T3 - 18C: 6E and T4 - 24C: 0E, C = clear and E = dark. Food management was carried out using commercial feed, containing 42% of corresponding crude protein, with the equivalent of 10% of live weight being offered. Measurements of the physical characteristics of the water were performed: temperature, dissolved oxygen (mg. L-1), salinity and pH. Biometric measurements were performed at the time of the distribution of individuals in the treatments and at 16 days after this action, obtaining in this case: total length, length of the cephalothorax, width and weight. With these data it was determined: mass gain (g), survival rate (%), specific growth rate (%), feed conversion factor (FCA) and condition factor (k). There were differences in temperature, pH and oxygen (p <0.05). Survival was significantly affected, with higher magnitudes of rates at 18C: 6E (69.2%) but similar (p <0.05) to 12C: 12E (68.5%). The exposure of L. vannamei post-larvae to photoperiods in short periods does not alter the biometric parameters of shrimp post-larvae. Further studies are needed to better understand the effect of the photoperiod and its results.